PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT),TEKNOLOGI INFORMASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT BPR NUSAMBA MENGWI-BADUNG - Ni Luh Gede Putu Purnawati (Jurnal Manajemen dan Bisnis, 2015)
Given the importance of employee performance, the issue which is of particular interestare the factors that influence it, among others, the training, information technology andmotivation. Otherwise in PT. BPR Nusamba Mengwi Badung an effort to get employers whohave the performance, have noticed the training, information technology and motivation.The formulation of the problem in this research is : whether the training influence on employeesperformance, whether the information technology influence on employees performance,whether the training influence on employees performance, whether information technologyinfluence on motivation, whether the training influence on motivation, whether the traininginfluence on information technology, whether the training influence on employees performanceby motivation and whether information technology influence on employees performance bymotivation in PT. BPR Nusamba Mengwi Badung, and to answer the problem, we conductedresearch with the study population of 75 employees at PT. BPR Nusamba Mengwi Badung. Themethod used is a method of population (census) and data collected by questionnaire. Theanalysis technique used is Path Analysis.Based on the results obtained conclusions include : there is significant influencebetween the training to employee performance, there is significant influence betweeninformation technology to employee performance, there is significant influence between thetraining to motivation, there is significant influence between information technology tomotivation, there is significant influence between the motivation to employee performance,there is significant between the training to information technology, there is significantinfluence between the training to employee performance by motivation and there is significantinfluence between information technology to employee performance by motivation in PT. BPRNusamba Mengwi Badung.Keyword : the training, information technology, motivation and performance